Effects of dried distillers grains with solubles on growth performance and fat quality of finishing pigs - J M Benz; S K Linneen; Joel M DeRouchey; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2007)
A total of 1,112 pigs were used in a 78-d growth assay evaluating the effects of increasing dried distillers grains with solubles (DDGS, 0, 5, 10, 15, or 20%) on pig growth performance and carcass characteristics. At the end of the trial, jowl fat, belly fat, and backfat samples were collected and analyzed for fatty acid profile and iodine value (IV). From d 0 to 78, ADG and ADFI decreased (linear; P<0.04) with increasing DDGS with the greatest reduction occurring between pigs fed 15 and 20% DDGS. Feed efficiency tended to improve (P<0.06) for pigs fed 5% DDGS compared with those fed other dietary treatments. Increasing DDGS decreased (P<0.04) carcass weight and percent yield. There was no difference (P>0.22) in loin depth, but increasing DDGS tended to decrease (P<0.09) backfat and fat-free lean index (FFLI). Backfat, jowl fat, and belly fat iodine values and percentage C 18:2 fatty acids increased (linear, P<0.02) with increasing DDGS in both the "toppped" pigs marketed 21 d before trial conclusion and pigs marketed at trial completion. Increasing DDGS decreased (linear, P<0.05) percentage saturated fatty acids in backfat and belly fat in both marketing groups and percentage saturated fatty acids in jowl fat with increasing DDGS in the diet in the pigs marketed at trial completion. Barrows had decreased (P<0.04) belly fat iodine values and percentage 18:2 fatty acids when compared to gilts. Barrows also had increased (P<0.05) jowl fat and belly fat percentage 18:2 fatty acids when compared to gilts. Based on these results and previous research trials, dried distillers grain with solubles from this source can be fed up to 15% before seeing reductions in ADG; however, the increase in iodine value and decrease in dressing percentage must be considered in determining the economic value of DDGS.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Swine; DDGS; Feed ingredients; Pork quality